VISUAL QUALITY AND THUMBNAILS: HOW E-COMMERCE PLATFORMS SHAPE CONSUMER PURCHASE BEHAVIOR - Jazzlynne Kenzie Santoso; Hajar; Whitney Laurens; Putri Cahyati; Nivi Fictorianus; Michael Ricky Sondak (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study investigates the influence of product visual quality, with a specific focus on product thumbnails, on consumer purchasing behavior across two leading e-commerce platforms in Indonesia. Employing a quantitative methodology using Partial Least Squares Structural Equation Modeling (PLS-SEM), data were gathered from 150 active online shoppers in South Sulawesi. The findings demonstrate that product visual quality exerts a significant, direct impact on consumer purchasing behavior, emphasizing that clear and appealing visuals foster consumer trust and mitigate perceived risks. Furthermore, the visual quality of thumbnails not only enhances the perceived value of products but also bolsters the overall credibility of the platform, serving as both informational cues and trust signals. These results corroborate the Stimulus-Organism-Response (S-O-R) framework, demonstrating that high-quality visual function serves as a stimulus that influences consumer perceptions and purchasing intentions. This research contributes to the expanding body of digital marketing literature by reaffirming that visuals are not merely decorative elements but are essential in motivating online purchasing behaviors. Practical implications advise e-commerce managers to prioritize consistent, high-resolution imagery and an intuitive platform design to sustain consumer confidence and boost sales conversions.